Micro, small and medium business and their adaptation to occupational health and safety regulations - Falconi Agapito, Fabiola (2020)
In 2017, according to official statistical data, the formal MIPYME (micro, small and medium-sized companies, for its initials in spanish), were estimated at 1.9 million, with business management being the point where the workforce generated in Peru. However, they would also be related to organizational failure facing challenges continuously, one of the biggest is how to approach legal compliance. To face these challenges and not fail, the following must be taken into account: - Responsible business culture with financial access. - Internal and external organizational environment with clear and simple compliance rules. - Adaptation to legal regulations The objective of this research is to try to integrate the main standards of OSH together with the statistical information National Institute of Statistics and Informatics-INEI, for this it is necessary to understand the benefits of the OSH Management System. In the initial phase of the article, we will present parameters prioritizing three aspects such as: 1) OSH diagnoses; 2) legal framework; 3) OSH Management System with structure and application guidelines. Below for all MIPYME, we will present the statistical analysis of the results with a practical example to verify the functionality of the system, which we will finally explain in the conclusions and recommendations.